GE_GERICHTE P/17492/2024 vom 4. Oktober 2024 - GE Cour de justice (2024)
ORDONNANCE PÉNALE;SIGNATURE;E-MAIL;CONTRAVENTION;FICTION DE LA NOTIFICATION;NOTIFICATION IRRÉGULIÈRE;DOMICILE À L'ÉTRANGER | CPP.110; CPP.354; CPP.85; CPP.87